2021
DOI: 10.1187/cbe.19-12-0271
|View full text |Cite
|
Sign up to set email alerts
|

“I Like and Prefer to Work Alone”: Social Anxiety, Academic Self-Efficacy, and Students’ Perceptions of Active Learning

Abstract: Two psychological variables, social anxiety (psychological distress relating to the fear of negative evaluation by others) and academic self-efficacy (confidence in one’s ability to overcome academic challenges) are linked with student perceptions of active-learning practices and final grades in a course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…Student Suggestions for Instructors about How to Reduce Anxiety in Large-Enrollment Online Science Courses Decreasing student anxiety can result in an increase in student motivation and performance (McKeachie, 1951;Culler and Holahan, 1980;Fletcher and Carter, 2010;Vitasari et al, 2010;England et al, 2017England et al, , 2019Hood et al, 2021). Many of the strategies that students in this study identified to reduce anxiety in online college science courses are further supported by the literature and may provide instructors with effective ways of mitigating student anxiety.…”
Section: 5% (221)mentioning
confidence: 62%
See 3 more Smart Citations
“…Student Suggestions for Instructors about How to Reduce Anxiety in Large-Enrollment Online Science Courses Decreasing student anxiety can result in an increase in student motivation and performance (McKeachie, 1951;Culler and Holahan, 1980;Fletcher and Carter, 2010;Vitasari et al, 2010;England et al, 2017England et al, , 2019Hood et al, 2021). Many of the strategies that students in this study identified to reduce anxiety in online college science courses are further supported by the literature and may provide instructors with effective ways of mitigating student anxiety.…”
Section: 5% (221)mentioning
confidence: 62%
“…High levels of student anxiety have been shown to negatively affect student motivation and performance in college (McKeachie, 1951;Culler and Holahan, 1980;Fletcher and Carter, 2010;Vitasari et al, 2010;England et al, 2017England et al, , 2019Hood et al, 2021). Student anxiety may be particularly detrimental in science courses owing to the rigor and difficulty of the material (Udo et al, 2004;Mallow, 2006) and the competitive, chilly and sometimes hostile environments (Seymour and Hewitt, 1997;Brainard and Carlin, 1998;Wyer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as noted by Hacisalihoglu et al (36), other recent studies indicate that it is the active learning itself, whether in a high-or lower-tech classroom, that matters (37,38). Yet, faculty must remember that students with social anxiety (39) or disabilities (40) may be averse to certain forms of active learning. Most importantly, faculty/instructors need to continually consider who the students are and what the best ways are to help them learn, and they must ensure that students have an appropriate environment (also see Section 5) for successful learning.…”
Section: Physical Spaces and Active Learningmentioning
confidence: 96%